2014
DOI: 10.1200/jco.2014.32.18_suppl.lba4
|View full text |Cite
|
Sign up to set email alerts
|

First results from the phase III ALTTO trial (BIG 2-06; NCCTG [Alliance] N063D) comparing one year of anti-HER2 therapy with lapatinib alone (L), trastuzumab alone (T), their sequence (T→L), or their combination (T+L) in the adjuvant treatment of HER2-positive early breast cancer (EBC).

Abstract: LBA4 Background: Lapatinib (L) is a HER1-HER2 tyrosine kinase inhibitor. The Adjuvant Lapatinib and/or Trastuzumab Treatment Optimisation (ALTTO) Trial is a randomised, phase III trial comparing 3 oral L-containing regimens with T, each given for 1 year. Methods: From June 2007 to July 2011, 8381 patients (pts) were randomised from 946 sites in 44 countries to receive either L+T, T→L, L, or T. Anti-HER2 therapy was initiated after completing all chemotherapy (N=4613), concurrently with a taxane following anth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 0 publications
1
62
1
1
Order By: Relevance
“…The tolerability of XT was better in NSABP-B40 when these agents were administered before AC (21). Even with 70% of the patients having node-positive disease, the number of DFS events was much lower than expected, as has been observed in a number of adjuvant breast cancer trials (27)(28)(29)(30). This low event rate substantially decreased the power of the study to show superiority of the AC!XT arm.…”
Section: Discussionmentioning
confidence: 91%
“…The tolerability of XT was better in NSABP-B40 when these agents were administered before AC (21). Even with 70% of the patients having node-positive disease, the number of DFS events was much lower than expected, as has been observed in a number of adjuvant breast cancer trials (27)(28)(29)(30). This low event rate substantially decreased the power of the study to show superiority of the AC!XT arm.…”
Section: Discussionmentioning
confidence: 91%
“…The FDAled meta-analysis of 12 neoadjuvant clinical trials (CTNeoBC) confirmed the patient-level prognostic value of pCR, but it could not demonstrate a significant correlation between pCR OR and event-free survival HR at the trial level across the studies (16). More recently, the ALTTO adjuvant trial (n ¼ 6,281) that compared 1 year of anti-HER2 therapy with lapatinib alone, trastuzumab alone, or the combination of the two drugs concomitant with or after chemotherapy in HER2-positive early breast cancer also failed to show statistically significant improvement in survival (17), despite a significant improvement in pCR rate (51% vs. 29% and 24%) with the dual HER2 blockade in the neoadjuvant NeoALTTO trial (18). Clearly, substantial and statistically significant improvements in pCR rate can translate in minor, nonsignificant improvements in patient survival in large trials.…”
Section: Introductionmentioning
confidence: 93%
“…Following early combinatorial trials in the metastatic HER2 setting, investigators rapidly moved this combination into thesome and a disappointment to all: a small, non-statistically improved disease-free survival (compared with trastuzumab) accompanied by substantial toxicity (9). However, it is important to note that just 555 disease-free events had occurred at 4.5 years, which fell far short of the 850 that were needed to achieve the desired power in the statistical plan.…”
mentioning
confidence: 99%